Leveraging Strategic Marketing Intelligence for Business Growth - Khan, Jeba (Journal of Advanced Research in Strategic Marketing Intelligence and Customer Engagement Optimization, 2025)
In an increasingly competitive and data-driven world, businesses must tap into the power of strategic marketing intelligence (MI) to gain a competitive edge. Strategic marketing intelligence is essential for understanding market trends, consumer behavior, competitive positioning, and overall business performance. This review explores how businesses can leverage MI to drive growth and achieve strategic objectives. It discusses the key tools and technologies, such as data analytics, artificial intelligence (AI), and machine learning, that are transforming the marketing landscape. Additionally, the article examines best practices, challenges, and ethical considerations associated with the use of MI in strategic decision-making.